A New Root-Finding Method for Univariate Non-Linear Transcendental Equations With Quadratic Convergence - Mahesh, G.; Triveni, V.S.; Swapna, G.; Venkateshwarlu, K. (Communications in Mathematics and Applications, 2022)
This paper presents a new algorithm to find a non-zero real root of the non-linear transcendental equations. The proposed method is based on the combination of the inverse sine series and Newton-Raphson method. Implementation of the proposed method in MATLAB is applied to different problems to ensure the methods applicability. Error calculation has been done for available existing methods and the proposed method. The suggested method is evaluated using a number of numerical examples and the results indicate that the proposed method is effective than well-knownmethods. The proposed method’s convergence is discussed, and it is shown to be quadraticallyconvergence.
Keywords: Non-linear equations; quadratic convergence; Root-finding; Iteration method